1.Wykonaj mnożenie i zredukuj wyrazy podobne
a) (x-1) (x [do potęgi 3] + x [do potęgi 2] + x + 1 )
b) (x+1) (x [ do potęgi 3 ] - x [do potegi 2] + x - 1)

2. Zapisz w postaci sumy algebraicznej
a) (x+1)(x+2)(x+3)
b)(x-2)(x+5)(2x-1)
c)(x-4)(x+1) [ do potęgi 2]
d) (2x-3) [do potęgi 2] (x+2)

2

Odpowiedzi

2009-12-02T19:16:39+01:00
X-1 x<3>+ x <2> +x+1 = 2x + x<3>+ x <2>

zad 2
a) 3x+6
b) 4x-4
c)2x-3 <2>
d)3x-1 <2>
2009-12-02T19:22:46+01:00
1
a)=x⁴+x³+x²+x-x³-x²-x-1=x⁴-1
b)=x⁴-x³+x²-x+x³-x²+x-1=x⁴-1
2
a)=(x²+2x+x+2)*(x+3)=x³+3x²+2x²+6x+x²+3x+2x+6=x³+6x²+11x+6
b)=(x²+5x-2x-10)*(2x-1)=2x³-x²+6x²-3x-20x+10=2x³+5x²-23x+10
c)=(x-4)*(x²+2x+1)=x³+2x²+x-4x²-8x-4=x³-2x²-7x-4
d)=(4x²-12x+9)*(x+2)=4x³+8x²-12x²-24x+9x+18=4x³-4x²-15x+8